(untitled) (Fiep Bulletin - online, 2014)
This Project seeks to integrate scientific know-how into popular knowledge in university extension. This academic article’s objective is to describe the experiences undergone in the Project “Health Education in Project Pescar.” Along these lines, we seek to integrate teaching, research and extension into the transformations experienced with a group of socially vulnerable teenagers, by way of health education as a form of care and prevention, aiming at transforming these teens into healthy citizens that participate in their own professional training for inclusion in the job market. The methodology used was a qualitative approach, with a description of an experience involving the participation of a group of extension-course scholars from Project Pescar’s Nursing and Physical Education courses, developed in a partnership between the University and the Gerdau Cosigua Steel Plant. During Project Pescar’s workshops, we discussed themes such as Physical Health; Physical Activities for Adolescents; Health and Social Problems; Sexual, Psychological and Mental Health; Environmental Health; Accident Prevention; and First Aid. The results indicate that university extension made a teaching-learning space possible, for both the academics and adolescents involved in it. We believe that health education conducted via extension courses – as an educational space focused on CARING FOR THE BODY and as a form of PRODUCTING KNOWLEDGE – helps individuals make intelligent choices, decisions and changes in their lives, to achieve life quality and active citizenship, independent of existing socio-economic conditions.